PLANT DENSITY AND NITROGEN SOURCES ON THE BEAN FARMING - Lima, R. T.; Nascimento, V.; Andreani Junior, R. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Nitrogen (N) is the nutrient absorbed in higher quantities and its dynamics is complex soil-plant system, moreover, the density of plants on cultivation of beans "winter" is variable in different soil and climatic conditions, requiring more consistent information. Thus, this study aimed to quantify what the best sources of N in coverage and optimal plant density on the growth and bean productivity "winter" in conventional tillage in a Alfissol. The work was developed in the city of Ferndale, SP, during the autumn-winter crop in 2014, a Red Ultisol sandy texture, in a randomized complete block arranged in a 4x3 factorial design with four replications. The treatments were a combination of four sources of N (absence of N, conventional urea, ammonium sulfate andmixture (50% N ammonium sulfate + 50% N urea)) with three plant densities (4, 6 and 8 plants per linear meter). The application of N sources ammonium sulfate and the mixture coverage in beans "winter" with the density of 4 plants linear meter, provided increases in dry weight and number of pods plant-1bean. In the absence of nitrogen in decreased densities of plants and productivity of bean grains. The three sources of nitrogen in the density of 8 plants per meter resulted in increases in grain yield in common bean